A monetary policy strategy in good and bad times: lessons from the recent past - Stephan Fahr; Roberto Motto; Massimo Rostagno; Frank Smets; Oreste Tristani (European Central Bank (ECB), 2011)
We evaluate the ECB's monetary policy strategy against the underlying economic structure of the euro area economy, in normal times and in times of severe financial dislocations. We show that in the years preceding the financial crisis that started in 2007 the strategy was successful at ensuring macroeconomic stability and steady growth despite shocks to the supply side and to the transmission mechanism which complicated the policy process. Emphasis on monetary indicators in the ECB's monetary policy strategy – the monetary pillar – was instrumental in avoiding more volatile and less predictable patterns of inflation and growth. After the collapse of financial intermediation in late 2008, the strategy of the ECB was to preserve the integrity of the monetary policy transmission mechanism by adopting a comprehensive package of non-standard policy measures. According to our quantitative evaluation of the impact of the non-standard policy package, which notably did not include entering commitments regarding the future path of the policy rate, the liquidity interventions decided in October 2008 and in May 2009 were critical to preserving price stability and forestalling a more disruptive collapse of the macro-economy.
Keywords: E31; E44; E51; E58; 330; credit; financial crisis; monetary policy; monetary transmission; Non-standard policy measures; Supply factors